A Multimodal Discourse Analysis of Sexual Violence Representation by the Social Media in Indonesia - Annisa Dwi Kusuma Hany; Dhea Dasa Cendekia Zairin; Rizki Aditya Putra; Konselia D. Vera (INJECT (Interdisciplinary Journal of Communication), 2025)
This research aims to analyze how the Instagram account @drg.mirza, as a form of citizen journalism, constructs the representation of sexual violence through a multimodal approach. This study provides an in-depth understanding of digital communication strategies in advocating for social issues. Employing a qualitative method with a multimodal analysis approach, data was collected through screen captures and screen recordings of Instagram Story posts. The data analysis was based on the framework of Systemic Functional Linguistics (SFL) by Halliday & Matthiessen for the verbal aspects, and multimodality theory by Kress & Van Leeuwen for the visual aspects, reinforced by Danesi's emoji theory. The results indicate that the sexual violence narrative is built through the strategic integration of verbal and visual elements. The account combines an informative declarative mood with an action-mobilizing imperative mood and uses a dynamic gaze and other visual elements to create emotional proximity and encourage audience participation. Theoretically, this study contributes to the understanding of the adaptation of linguistic and multimodality theories in digital communication.